Glutathione S-Transferase Gene Family in Gossypium raimondii and G. arboreum: Comparative Genomic Study and their Expression under Salt Stress - Dong, Yating; Li, Cong; Zhang, Yi; He, Qiuling; Daud, Muhammad K.; Chen, Jinhong; Zhu, Shuijin (Frontiers in Plant Science, 2016)
Glutathione S-transferases (GSTs) play versatile functions in multiple aspects of plant growth and development. A comprehensive genome-wide survey of this gene family in the genomes of G. raimondii and G. arboreum was carried out in this study. Based on phylogenetic analyses, the GST gene family of both two diploid cotton species could be divided into eight classes, and approximately all the GST genes within the same subfamily shared similar gene structure. Additionally, the gene structures between the orthologs were highly conserved. The chromosomal localization analyses revealed that GST genes were unevenly distributed across the genome in both G. raimondii and G. arboreum. Tandem duplication could be the major driver for the expansion of GST gene families. Meanwhile, the expression analysis for the selected 40 GST genes showed that they exhibited tissue-specific expression patterns and their expression were induced or repressed by salt stress. Those findings shed lights on the function and evolution of the GST gene family in Gossypium species.